STATUS KEBERSIHAN MULUT DAN PERILAKU MENYIKAT GIGI ANAK SD NEGERI 1 MALALAYANG - Gopdianto, Randy; Rattu, A. J. M; Mariati, Ni Wayan (Universitas Sam Ratulangi, 2015)
Abstract: Mouth is an ideal place for bacteria growth because of temperature, moisture and leftovers. Dental and oral hygiene is determined by leftovers (food debris), plaque, calculus and stains on the surface of the tooth. In an effort to maintain dental and oral hygiene, preferable given since elementary school age because that age is an ideal momentto train the child’s ability to brush teeth. The purpose of this research is to know the status of dental and oral hygiene according to the habit of brushing teeth before going to bed at night in SD Negeri 1 Malalayang. Method of this study was descriptive study with cross-sectional design. Sample was taken by giving a questionnaire to find out the behavior of brushing teeth and do the OHIS examination according to Green and Vermillion to the students of class IV, V dan VI. Result of the study showed, the majority of respondents were female 35 people (64%) and male 20 people (36%), based on age of the respondents are aged 8 years 7 people (13%), 9 years old 12 people (22%), 10 years old 25 people (45%) and 11 years old there were 11 people (20%). Based on the assement of the examination OHIS, 35 respondents has goog result (64%), 15 respondents had moderate result (27%) and 5 respondents had poor result (20%). Conclusion: Students in grade IV, V and VI have good dental and oral hygiene.Keywords: oral hygiene status, brushing teeth behaviorAbstrak: Mulut merupakan suatu tempat yang ideal bagi perkembangan bakteri karena temperatur, kelembapan dan sisa makanan. Kebersihan gigi dan mulut ditentukan oleh sisa makanan (food debris), plak, kalkulus, dan noda (stain) pada permukaan gigi. Dalam usaha menjaga kebersihan mulut sebaiknya diberikan sejak usia sekolah dasar karena usia tersebut merupakan saat yang ideal untuk melatih kemampuan anak termasuk menyikat gigi. Tujuan penelitian ini ialah untuk mengetahui status kebersihan mulut menurut kebiasaan menyikat gigi sebelum tidur malam pada anak di SD Negeri 1 Malalayang. Penelitian ini bersifat deskriptif dengan rancangan yang digunakan ialah cross sectional. Pengambilan sampel dengan cara memberikan kuesioner untuk mengetahui perilaku menyikat gigi dan melakukan pemeriksaan OHIS menurut Green and Vermillion pada siswa-siswi kelas IV, V dan VI. Hasil penelitian menunjukkan sebagian besar respoden berjenis kelamin perempuan 35orang (64%) dan jenis kelamin laki-laki 20 orang (36%). Berdasarkan usia terdapat responden umur 8 tahun 7 orang (13%), umur 9 tahun sebanyak 12 orang (22%), kemudian usia 10 tahun mempunyai 25 orang (45%), dan umur 11 tahun terdapat 11 orang (20%). Berdasarkan penilaian dari pemeriksaan OHIS sebanyak 35 responden (64%) berkategori baik, 15 responden (27%) berkategori sedang, dan berkategori buruk 5 responden (9%). Simpulan: Siswa-siswi kelas IV, V dan VI memiliki kebersihan gigi dan mulut yang baik.Kata kunci : status kebersihan mulut, perilaku menyikat gigi